2017
DOI: 10.1042/bst20170202
|View full text |Cite
|
Sign up to set email alerts
|

SNARE phosphorylation: a control mechanism for insulin-stimulated glucose transport and other regulated exocytic events

Abstract: Trafficking within eukaryotic cells is a complex and highly regulated process; events such as recycling of plasma membrane receptors, formation of multivesicular bodies, regulated release of hormones and delivery of proteins to membranes all require directionality and specificity. The underpinning processes, including cargo selection, membrane fusion, trafficking flow and timing, are controlled by a variety of molecular mechanisms and engage multiple families of lipids and proteins. Here, we will focus on cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Another role for ATP is in phosphorylation of protein substrates important for exocytosis. This topic is reviewed elsewhere in detail (Klenchin and Martin, 2000; Laidlaw et al, 2017; Kadkova et al, 2018).…”
Section: The Role Of Atp In Exocytosismentioning
confidence: 99%
“…Another role for ATP is in phosphorylation of protein substrates important for exocytosis. This topic is reviewed elsewhere in detail (Klenchin and Martin, 2000; Laidlaw et al, 2017; Kadkova et al, 2018).…”
Section: The Role Of Atp In Exocytosismentioning
confidence: 99%
“…Posttranslational modifications of secretion machinery proteins are known as powerful ways to regulate exocytosis. In contrast to the well-characterized serine/threonine phosphorylation, the importance of tyrosine phosphorylation in exocytosis has only recently begun to be appreciated (Cijsouw et al, 2014;Gabel et al, 2019;Jewell et al, 2011;Laidlaw et al, 2017;Meijer et al, 2018;Seino et al, 2009). In addition to the phosphorylation of NSF at its pY 83 site, recent studies have shown that tyrosine phosphorylation of MUNC18-3 at the pY 219 and pY 527 sites, Annexin-A2 at pY 23 , and MUNC18-1 at pY 473 actively participates in the vesicle release machinery to explicitly regulate exocytosis processes (Gabel et al, 2019;Jewell et al, 2011;Meijer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There are three major exocytosis pathways in secretory cells, namely, full-collapse fusion, kiss-and-run, and compound exocytosis, which possess different secretion rates and release amount (Sudhof, 2004). It has previously been reported that the phosphorylation of critical proteins at serine/threonine or tyrosine residues participates in stimulus-secretion coupling in certain important exocytosis processes, for example, the secretion of insulin from pancreatic β cells and the secretion of catecholamine from the adrenal medulla (Laidlaw et al, 2017;Ortsater et al, 2014;Seino et al, 2009). However, the exact roles of protein tyrosine phosphatases (PTPs) in the regulation of key hormone secretion procedures are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study highlighted the central role played by a complex of soluble-N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) in metabolic diseases, [8,9] which are also involved in the pathogenesis of type 2 diabetes mellitus (T2DM) [10] as well as in cardiac functions. [1113] The SNARE-complex includes the two t-SNARE proteins, synaptosomal protein of 25 kDa (SNAP25) and syntaxin 1A (Stx-1A), as well as the v-SNARE protein VAMP2.…”
Section: Introductionmentioning
confidence: 99%